STRUKTUR, KATEGORI DAN FUNGSI SOSIAL UNGKAPAN LARANGAN MENGENAI CINTA, PACARAN, DAN MENIKAH DI KENAGARIAN TOBOH SIKALADI KECAMATAN SINTUK TOBOH GADANG KABUPATEN PADANG PARIAMAN - Murni MS, Desy; Hayati, Yenni; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This study aimed to describe the structure and function of social expression of a ban on love, dating, and married in Kenagarian Toboh Sikaladi Kecamatan Sintuk Toboh Gadang Kabupaten Padang Pariaman. The research is a qualitative study using descriptive methods. Background or where the study was conducted in Kenagarian Toboh Sikaladi Sintuk Toboh Tower District of Padang Pariaman district. The informants consist of one main informant and two supportive informants. Data were collected through three stages, namely observation, interview and recording techniques. After that, the data is analyzed by a data inventory phase, phase description of the structure and a social function, stage identifies the data, and reporting stage. Based on the results, it can be concluded that data about people's trust ban expression of love, dating, and married in Kenagarian Toboh Sikaladi Kecamatan Sintuk Toboh Gadang Kabupaten Padang Pariaman found as many as 53 expression. The structure of the people's trust in the public ban Kenagarian Toboh Sikaladi Kecamatan Sintuk Toboh Gadang Kabupaten Padang Pariaman is divided into two forms,ie expression of belief and expression structured two-part folk beliefs structured three parts.The phrase structured ban two parts are found as many as 45 expression, whereas expression of a structured three parts found eight expression. This study included into the category of folk beliefs surrounding human environment of love, courtship, and marriage. The social function of the people's trust ban expression in this research, strengthen religious emotion and conviction found as many as five expressions, fantasy projection system found 31 expression, educate found three expressions, prohibit found 13 expression, and had found a phrase.Keywords: social expression, local beliefs, prohibition